Unraveling the physical and chemical contributions of SCMs to durability - Hemalatha, M.S.; Santhanam, Manu (Journal of Structural Engineering, 2024)
Supplementary Cementing Materials (SCMs) are integral to modern concrete construction. Their use brings inimmense value addition to the long term strength and durability, due to their contribution to the development of adisconnected pore structure. There have been several attempts in the past to identify specific physical and chemicalcontributions of SCMs to the compressive strength of concrete in order to evolve a rational approach towards decidingthe extent of substitution of cement. In this paper, an attempt has been made to describe the physical and chemicalcontribution of SCMs to durability properties of cement mortar using a methodology previously developed by thesame authors.